Efeito dos intervalos de recuperação entre séries de 1 e 3 minutos em exercícios resistidos até falha concêntrica em atletas de futebol da categoria sub 20: ensaio clínico randomizado - Massahud, Anderson Ranieri (2018)
Current researches have demonstrated that resistance training results in a variety of benefits to improve the quality of life, health, athletic performance and physical rehabilitation. Among the various training methods, the resistance training until the concentric failure is the one that has increased in recent years. The concentric failure indicates that the limit of repetitions for that load was reached. Thus, it is necessary a recovery interval for the realization of a new series. However, studies that compare the influence of different recovery intervals between series in this training method are scarce. The aim of this study was to evaluate the effect of two different recovery intervals between series (1 and 3 minutes) during the realization of a protocol of resisted exercises until concentric failure in soccer athletes. A randomized clinical trial was carried out with male football athletes from the category under - 20. Twenty-four men filled the inclusion requirements in this study, being twelve in each group. The first group performed the training protocol with 1 minute of interval (G1), while the second group with 3 minutes of interval between series (G3). The training program with resisted exercises until the concentric failure (75% of RM) lasted three weeks and one week of regenerative training (40% of RM). Furthermore, the frequency was three times a week with a minimum interval of 48 hours between sessions. The order of the training was chair extender, table flexor, leg press and squat. Three series of each exercise were carried out with their intervals and, only after the three series in the same exercise, the sequence was executed in the next exercise. Participants were evaluated through functional performance tests (Single/Triple Hop test and Vertical Jump); Electromyographic signal (RMS) through the maximum voluntary isometric contraction (MVIC) of the muscles rectus femoris, vastus medialis, vastus medialis, semitendinosus and biceps femoris; Peak Torque relativized by the body through the isokinetic dynamometry of the extensor muscles and knee flexors at the speed of 60º/second; Total number of repetitions during the training period until the concentric failure and the one repetition maximum test (1 RM) pre and post intervention. To compare the results, it was used the value of delta (∆) obtained from the comparison between the pre and post training values (post-value minus the pre-value = delta value). When it was observed normality of the data, these were analyzed by the T test. In contrast, it was used the Mann-Whitney test (intergroup) or Wilcoxon test (intragroup) for data that presented non-normal distribution. In addition, it was considered the significance level of p < 0,05. According to the results there was significant difference between the two groups for the RMS values of the electromyography; relative peak Torque in the evaluation by Isokinetic dynamometry, the total number of repetitions and the test of 1 repetition maximum. The experimental group of 3 minutes interval presented Δ values higher than the values of the group with 1 minute interval. No significant differences were found for the functional performance tests Single/Triple Hop test and Vertical Jump. In conclusion, the resistance training until the concentric failure with recovery intervals of three minutes between series are effective for increasing the total volume of training, muscle torque and activation of motor units when compared to training with one minute interval between the series.